Impact Modification and Toughening of Polystyrene: Part-1. Blending with Low and Medium Molecular Mass Elastomers - Davallo, M.; Pasdar, H.; Khosravi, M. (Asian Journal of Chemistry, 2010)
Rubber toughened polystyrene (RTPS) materials were prepared by blending polystyrene with two types of thermoplastic elastomer [styrene-ethylene-propylene-styrene (SEPS)] which include low molar mass and medium molar mass with the same styrene content. The effect of particle morphology, varying molar mass and percentage thermoplastic elastomer content on the fracture properties were evaluated. The properties of polystyrene modified with 30-40 % low and medium molar mass elastomers were found to be superior to those containing 10-20 % low and medium molar mass elastomers with phase morphology of 30-40 % medium molar mass blends show better distribution of rubber particles with reduced size within the PS phase.